Human Assets Index. Computing retrospective series from 1970 to 2008 - Catherine Korachais (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
The United Nations Committee for Development Policy (CDP) defines the Least Developed Countries (LDCs) as countries suffering from structural handicaps to economic development such as low income, low levels of human resources or capital, and high levels of structural economic vulnerability (UN 2008). The identification of LDCs is carried out according to predetermined thresholds on the three following criteria:(a) Gross National Income per capita (GNI per capita)(b) Human Assets Index (HAI)(c) Economic Vulnerability Index (EVI)Here we are interested in the level of human capital. The latter was initially measured by literacy rates, which was insufficient since it didn't take into account health levels. Then it was replaced from 1991 to 2002 by the Augmented Physical Quality of Life Index (APQLI). Since 2003, it was replaced by the Human Assets Index (HAI), which is more complete (for a historical review, cf. Guillaumont 2009, Caught in a trap, chap. 5).
Keywords: I31; I32; 330